The Reconstitution of Death Criminal Imposition against Persons of Criminal Actions on Narcotics Post-Decision of the Constitutional Court Number 2-3/PUU-V/2007 - Muhamad Romdoni (LEGAL BRIEF, 2022)
Many people consider the death sentence to be a violation of their human rights. For these and other reasons, petitioners Edith Yunita Sianturi, Rani Andriani (Melisa Aprilia), Myuran Sukumaran, Andrew Chan, and Scott Friedrich request that Anthony Rush file a judicial review petition against Articles 28A and 28I, paragraph (1) of the 1945 Constitution until the Constitutional Court Decision No. 2-3-PUU-IV/2007 is issued. This study employed normative juridical research, which is described as research that focuses on studying the rules or norms in the ius constitutum. The goal of this research is to rebuild the imposition of the death penalty following the Constitutional Court's judgment. For this inquiry, it was decided to take a state-level strategy. The fact that the state is willing to take stronger action, such as the imposition of capital punishment, against drug producers, dealers, and sellers because it has the potential to have a very negative impact on humanity demonstrates that the death penalty does not conflict with the 1945 Constitution of the Republic of Indonesia and the country's human rights principles.